Skin Metastasis of Gastrointestinal Stromal Tumors: A Case Series and Literature Review - Liu P; Tan F; Liu H; Ge J; Liu S; Lei T; Zhao X (Cancer Management and Research, 2020)
Peng Liu,* Fengbo Tan,* Heli Liu, Jie Ge, Sheng Liu, Tianxiang Lei, Xianhui Zhao Department of Gastrointestinal Surgery, Xiangya Hospital, Central South University, Changsha 410008, Hunan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Heli Liu Department of Gastrointestinal SurgeryXiangya Hospital, Central South University, Changsha 410008, Hunan, People’s Republic of ChinaTel +86 13874967285Email heliliu@csu.edu.cnBackground: Gastrointestinal stromal tumors (GISTs) extremely and rarely metastasize to the skin, and such metastases have not been well characterized.Methods: Retrospective analysis of clinicopathological data of patients with skin metastasis of a GIST (SM-GIST) admitted to Xiangya Hospital (Changsha, Hunan, China) and literature review were conducted.Results: Including our 4 cases, a total of 17 cases have been reported to date. The mean age of the patients was 55.4 years (29∼ 70 years) and there was not sex predominance (male 10 and female 7). Primary tumors were often located in the stomach (n=9), duodenum (n=2) and small bowel (n=2). Meanwhile, SM-GIST mainly occurred in head and face (n=6), extremities (n=6), followed by abdomen wall (n=5), back (n=3) and chest (n=2). Mutation analysis revealed that the frequency of wild-type GIST (WT-GIST), exon 9, 11 and 13 mutations was 6, 1, 4 and 1, respectively. The average time to SM-GIST was 4.22 years, specifically 4.59 years in gastric and 3.8 years in non-gastric. Moreover, for the resection only group (including chemotherapy), such average time was 3.63 years, while for the combined group (resection and tyrosine kinase inhibitors (TKIs)), it was about 4.74 years. The mean survival was approximately 6.2 years. However, after the diagnosis of SM-GIST, survival was only about 1.69 years.Conclusion: SM-GIST is a rare malignant condition. Non-gastric GIST, surgery without TKIs, high invasiveness and tumor burden, and molecular subtype (mutation in exon 9, 11 and wild-type) may be conducive to the development of SM-GIST. Additionally, it is also a sign of poor prognosis.Keywords: gastrointestinal stromal tumor, skin metastasis, tyrosine kinase inhibitors